If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + -8x = 36 Solving -4 + -8x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -8x = 36 + 4 Combine like terms: -4 + 4 = 0 0 + -8x = 36 + 4 -8x = 36 + 4 Combine like terms: 36 + 4 = 40 -8x = 40 Divide each side by '-8'. x = -5 Simplifying x = -5
| 8x-8=7x+14 | | -44=-3x-2 | | 2x+17=53 | | 8x-8=7x+4 | | -12=x-21 | | 4x-7=9x | | -57=-12+3x | | 29=-8x-3 | | 3-x=-4 | | 11-3v-u= | | 0.6x-0.8(3-x)=2.5 | | -3x=-10+2x | | y^2-18x=0 | | 9x=16+5x | | 6x-3=27x | | -6u-27=7(u-2) | | =-3[x+2]2+5 | | 5x+6=4x+5 | | 5(z-2)+4z-4= | | 4ln(x-7)=8 | | 5k-8=1(9) | | 2u-6=-2 | | Y^2+3y-6=0 | | 70=3w+16 | | 4(z-2)+8z-1= | | c=2.88(6)+14.18 | | 2(5z-1)-3(z-2)= | | x+7-15+(-4)=24 | | 5x/2-5x-10/10=0 | | 0.875h-0.625=2 | | 2(3m-7)-3(m-9)= | | (x-3)(x-3)=3 |